Inclusive Leadership and Equity Outcomes in Heterogeneous Primary Education - Nadiatul Hatimah; Adiyono Adiyono; Mabrouk Chibani Mansouri; Naila Widya Daryanti (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
Today, primary education increasingly embraces inclusive leadership as schools face growing diversity in students' academic levels, learning characteristics, and social backgrounds. Although policy and instructional literature widely discuss inclusion, empirical research rarely examines how school leaders enact inclusive leadership in everyday management practices. This study explores how equity-oriented leadership practices enhance inclusion in managing heterogeneous primary education learners. Using an exploratory qualitative case study design, we investigated inclusive leadership practices at SDTQ Anak Sholih through semi-structured interviews with school leaders and teachers, classroom observations, and analysis of institutional documents. The researchers conducted a thematic analysis to identify patterns and leadership practices related to equity and inclusion. The analysis revealed that school leaders operationalized inclusive leadership through four key approaches: equity-centered decision-making, differentiated classroom organization, restorative strategies for social dynamics, and distributed collaboration with teachers and parents. Notably, even in instances of limited parental engagement, equity-oriented leadership persisted, indicating that distributed leadership supports inclusive practices. The findings position inclusive leadership not merely as a normative ideal but as a dynamic systemic process with significant implications for both educational leadership theory and the inclusive management of diverse school classrooms.